1999
DOI: 10.1063/1.123809
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced brightness and efficiency in organic electroluminescent devices using SiO2 buffer layers

Abstract: Bright organic electroluminescent devices having a metal-doped electron-injecting layerOrganic electroluminescent devices using SiO 2 as a hole-injecting buffer have been fabricated. With the presence of the buffer, the luminance of the device reaches 1820 cd/m 2 at the current density of 20 mA/cm 2 , which corresponds to an efficiency of 9.1 cd/A. The enhancements in brightness and efficiency are attributed to an improved balance of hole and electron injections due to blocking of the injected holes by the buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(111 citation statements)
references
References 17 publications
0
110
0
1
Order By: Relevance
“…High-efficiency OLEDs have also been reported in various HIL/HTL configurations. [4][5][6][7][8] Furthermore, low-voltage and high-efficiency OLEDs can be realized with a p-doped HIL [9][10][11] in which the layer thickness can be readily adjusted for optimal light extraction. It has been suggested that the enhanced performance in HIL/HTL devices is due to a sequence of cascaded hole-injection barriers present in the HIL/HTL/ETL structure, which produces a "balanced" electron-hole recombination at the HTL/ETL interface.…”
mentioning
confidence: 99%
“…High-efficiency OLEDs have also been reported in various HIL/HTL configurations. [4][5][6][7][8] Furthermore, low-voltage and high-efficiency OLEDs can be realized with a p-doped HIL [9][10][11] in which the layer thickness can be readily adjusted for optimal light extraction. It has been suggested that the enhanced performance in HIL/HTL devices is due to a sequence of cascaded hole-injection barriers present in the HIL/HTL/ETL structure, which produces a "balanced" electron-hole recombination at the HTL/ETL interface.…”
mentioning
confidence: 99%
“…Thus, the improvement of the optical transmission is needed. Recently some inorganic materials, such as SiO 2 were introduced to OELDs to balance the number of holes and electrons injected to the emitter layer to achieve high recombination efficiencies [13]. An attempt to obtain better electric conduction properties has been made by insertion of a SiO 2 buffer layer between the poly (ethylene terephthalate) (PET) and ITO layers (ITO/SiO 2 /PET) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The introduced buffer layers mainly can be divided in inorganic and organic compounds. Among the reported inorganic anodic buffer layers good inorganic insulators such as transparent metal oxides Pr 2 O 3 , Y 2 O 3 , Tb 4 O 7 , ZnO (Xu et al, 2001), Al 2 O 3 (Li et al, 1997;Xu et al, 2001), SiO 2 (Deng et al, 1999;Xu et al, 2001), silicon nitride Si 3 N 4 (Jiang et al, 2000;Xu et al, 2001), carbon nitride a-C:N , transition metal oxides, also V 2 O 5 , Guo et al, 2005), MoOx (You et al, 2007;Jiang et al, 2007), WO 3 , Meyer et al, 2007), CuOx, (Hu et al, 2002;Xu et al, 2001), NiO, (Chan et al, 2004;Im et al, 2007) and Ta 2 O 5 (Lu & Yokoyama, 2003), have attracted much attention due to their capability to lower the hole-injection barrier and improve the interface morphology.…”
Section: Hole Transporting and Buffer Layersmentioning
confidence: 99%